Proteasomes tether to two distinct sites at the nuclear pore complex - Albert, Sahradha; Beck, Martin (Proceedings of the National Academy of Sciences of the United States of America, 2017)
The partitioning of cellular components between the nucleus and cytoplasm is the defining feature of eukaryotic life. The nuclear pore complex (NPC) selectively gates the transport of macromolecules between these compartments, but it is unknown whether surveillance mechanisms exist to reinforce this function. By leveraging in situ cryo-electron tomography to image the native cellular environment of Chlamydomonas reinhardtii, we observed that nuclear 26S proteasomes crowd around NPCs. Through a combination of subtomogram averaging and nanometer-precision localization, we identified two classes of proteasomes tethered via their Rpn9 subunits to two specific NPC locations: binding sites on the NPC basket that reflect its eightfold symmetry and more abundant binding sites at the inner nuclear membrane that encircle the NPC. These basket-tethered and membrane-tethered proteasomes, which have similar substrate-processing state frequencies as proteasomes elsewhere in the cell, are ideally positioned to regulate transcription and perform quality control of both soluble and membrane proteins transiting the NPC.